Student Attitudes Toward Accelerated Reader: "Thanks for asking!" - Amy Smith; Karen Westberg (Arizona State University, 2011)
The Accelerated Reader program was designed by Renaissance Learning to increase studentsâ motivation to read and studentsâ achievement in reading; however, a review of the literature reveals inconsistent findings about its outcomes. The Renaissance Learning company reports several research studies on their website that suggest the program is meeting its goals. Independent research studies about studentsâ attitudes toward the program, however, have been varied, some reporting favorable attitudes toward the program and others indicating unfavorable results. What do students really think about the Accelerated Reader program, a widely used supplemental, independent reading program in which students read fiction and non-fiction books of their choice and take brief online comprehension quizzes about the books? The results from our study on studentsâ attitudes toward AR in Grades 3-8 from student focus group interviews are described in this article.